Pemanfaatan Koleksi Museum Negeri Provinsi Sulawesi Tenggara Sebagai sumber Belajar Sejarah Pada Peserta Didik Di SMA Negeri 3 Kendari - Harnisa, Susi; Urlialy, Gesia Mira; Kapitanhitu, Reihana (Program Magister Pendidikan Sejarah FISH UNJ, 2024)
The method in this research is descriptive qualitative. This research was conducted at SMA Negeri 3 Kendari and the State Museum of Southeast Sulawesi Province located in Kendari city, Southeast Sulawesi province. Data collection techniques consisted of 3 parts, namely observation, interviews and documentation. Data sources were obtained both primary and secondary, so it needs validation. Data validity was done by triangulating sources and triangulating techniques. The data analysis technique used is the Miles & Huberman model which consists of 3 activity streams, namely data reduction, data presentation, and conclusion drawing/verification. The results of this study indicate that: The State Museum of Southeast Sulawesi Province can be used as a history learning resource. This is because the State Museum of Southeast Sulawesi Province has 10 types of collections, namely: collections of geology, biology, ethnography, archaeology, history, numismatics, philology, various ceramics, Fine Arts and Technology. Some of the museum collections can be utilised as learning resources for class X history at SMA Negeri 3 Kendari, Southeast Sulawesi on specialisation history material and compulsory history in the 2013 curriculum. Teachers can utilise museum media as an alternative learning method in learning history through museum collections, namely the tour work method. Keywords: Museum, Learning Resources, History